The Number of Chains of Subgroups of the Group Zm ×Sn,n ≤ 5,m ≤ 3 (2021)
The study of chains of subgroups in this paper describes the set of all chains of subgroups of G that end in G which is used to solve many computational problems in fuzzy group theory. It is also showed that a fuzzy subgroup is simply a chain of subgroups in the lattice of subgroups.